Burnout, Job Satisfaction and Job Autonomy as Determinants of Abandonment Intent and Job Retention of Nurses and Nursing Assistants - Garrido, Olga; Maulen, Gladys; Raineri, Andrés (Estudios de Administración, 2017)
This study analyzes the antecedents of intentions to leave and/or stay in the organization, in a sample of nurses and nursing aides employing a survey methodology. Results suggest that higher levels of burnout, lower levels of satisfaction with pay, and lower levels of work autonomy are associated with intents to leave both among nurses and nursing aides. Furthermore, in the case of nurses, the flexibility of their work shift schedule explains additional variance of intentions to leave. Increasing age explains additional variance in nursing aides’ intention to leave. Intentions to remain in the organization are explained by schedule flexibility and autonomy at work in the case of nurses, and lower levels of emotional exhaustion and higher levels of fulfillment at work in the case of nursing aides.